-v + 5 + 6v = 1 + 5v + 3Clean up and combine each side:(-v + 6v) + 5 = (1 + 3) + 5v5v + 5 = 4 + 5vSubtract 5v from each side:5 = 4.There is no solution.No value of 'v' can make [ 5 = 4 ].
what is 5(x-5) plus 6 expanded and simplified
It is: 5+4w simplified
It is an expression that can be simplified to: 76p-5
-5 + -3x + -x + 16-4x + 11
-v + 5 + 6v = 1 + 5v + 3Clean up and combine each side:(-v + 6v) + 5 = (1 + 3) + 5v5v + 5 = 4 + 5vSubtract 5v from each side:5 = 4.There is no solution.No value of 'v' can make [ 5 = 4 ].
what is 5(x-5) plus 6 expanded and simplified
Simplified: 5+1x
It is: 5+4w simplified
It is an algebraic expression that can be simplified to: 11x+5
6 + 2x + 5 = 11 + 2x
5(6v + 7)(6v - 7)
It is an expression that can be simplified to: 76p-5
It is: 7a+1 when simplified
-5 + -3x + -x + 16-4x + 11
7x-9
It is: 10+5 = 15